Color-ornamental Plants Cultivation for Metal Waste Reduction on Mining Sites and Their Biorecovery of Metals - Shobirin, Rizky Arief; Daroini, Ahsin; Suwasono, Edy (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary Sciences, 2020)
Metals, Minerals and Rock as minerals, are important aspects in the economic and social development of a country. However, due to the lack of communication between the private sector as a miner and the government as a supervisory party, there has been a lot of illegal mining occurring and no effort to revise the environment so that it has an impact on people's welfare and environmental pollution that is increasingly high. So as to reduce the level of environmental pollution that is currently needed there is the processing of mining waste. The metal will form complex bonds of coordination with ligands and form compounds of a certain color. By knowing the nature of these plants, the selection of plants that have a tendency to bind metal ions can be complexly coordinated to reduce the waste of metal ions generated from mining processing activities or on mining sites.